\( \frac{7(x-3)}{x-4}+\frac{5}{x}=\frac{-5}{x(x-4)} \) Solve the following equation by factoring. A. The solution set is \( \{ \). (Type an integer or a simplified fraction. Use a comma to separate answers as needed.) B. There is no solution.
Real Tutor Solution
Answer
Solution
Reviewed and approved by the UpStudy tutoring team
Beyond the Answer
To solve the equation \( \frac{7(x-3)}{x-4}+\frac{5}{x}=\frac{-5}{x(x-4)} \), we first find a common denominator, which is \( x(x-4) \). Multiplying through by the common denominator eliminates the fractions: \[ 7(x-3)x + 5(x-4) = -5 \] Next, we distribute and combine like terms: \[ 7x^2 - 21x + 5x - 20 = -5 \] This simplifies to: \[ 7x^2 - 16x - 15 = -5 \] Bringing -5 over gives: \[ 7x^2 - 16x - 10 = 0 \] Now, we can either factor or use the quadratic formula. In this case, we can factor the quadratic: \[ (7x + 5)(x - 2) = 0 \] Setting each factor to zero gives: 1. \( 7x + 5 = 0 \rightarrow x = -\frac{5}{7} \) 2. \( x - 2 = 0 \rightarrow x = 2 \) However, we must check for extraneous solutions by substituting back into the original equation. \( x = -\frac{5}{7} \) does not create any undefined expressions, whereas \( x = 2 \) also checks out without undefined expressions. Hence, the solution set is: A. The solution set is \( \{-\frac{5}{7}, 2\} \).